Backstory [large type] - Davis, Susan Page (Skirmish Cove Mysteries, 2023)
"A small, themed bed & breakfast on the Maine coast sets the scene for murder. A hurricane lashes the Novel Inn, forcing guests to remain beyond their check-out dates. Kate's ex-fiancé from ten years ago has booked a room and she is trying to avoid him. Jillian moves her sick elderly neighbor to the inn so she can take care of him. Then the power goes out and they are faced with providing all meals for their guests, not just breakfast. When the guest in the Hercule Poirot Room fails to show for supper, Jillian and Kate go to check on him and make a grisly discovery. With a murdered guest and items disappearing around the inn, it's time for the Gage siblings and the local police to go into action."--